Ergonomic Risk Assessment Among Warehouse Workers in a Logistics Company - Ruslan, Amira Wildayati; Rahim Jamian; Zulkarnain Zulkifli (Progress in Engineering Application and Technology, 2024)
The logistics industry plays a crucial role in global economic development but faces challenges related to ergonomics and musculoskeletal disorders (MSDs). Warehouse and logistics workers often perform physically demanding tasks, increasing the risk of work-related musculoskeletal disorders (WMSDs). This comprehensive project aims to identify the prevalence of WMSDs among warehouse workers in a logistics company, assess associated ergonomic risk factors, and propose physical ergonomic interventions using rapid entire body assessment (REBA) analysis. Various methods, including a questionnaire survey, Initial ERA Checklist, and ERA Employee Assessment Worksheet, were utilized to gather data for this study. These tools enabled the collection of comprehensive information from warehouse workers. To analyze the collected data, descriptive statistical analysis was conducted, and software tools such as SPSS, Initial ERA Score, Reba Score, and Kinovea Software were employed. This analytical approach allowed for a detailed examination of the data and provided valuable insights into the ergonomic risk assessment among warehouse workers. The results indicate that Workers X, Y, and Z fall into the medium-risk category, emphasizing the need to address job-specific issues for overall workplace health improvement. The logistics company, recognizing the importance of worker safety, conducted proactive checks, and proposed tailored changes, such as workstation adjustments and regular training sessions. In conclusion, these formal recommendations for future research aim to address the challenges faced by researchers in comprehending every risk factor and communicating effectively with workers regarding ergonomics. This contribution is envisioned to enhance scholarly knowledge and foster advancements in promoting safe and healthy work environments.